2021
DOI: 10.2478/emj-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring economic efficiency of flexible fixtures in multiproduct manufacturing

Abstract: The first-priority directions for modern engineering, especially for multiproduct manufacturing, include the intensification of manufacturing processes, increasing the efficiency of technological equipment, and reducing the time required to implement technological solutions. Fixture design is a complicated and time-consuming process that requires considering many parameters of the closed-loop technological system “machine tool — fixture — cutting tool — workpiece”. One machined part can have several fixture la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Ivanov et al [54] developed new flexible fixtures to manufacture three different types of parts: levers, forks, and connecting rods. Ivanov et al [55] further analyzed and demonstrated the economic benefits of using flexible fixtures, which can effectively support small-batch productions with frequent changes of tools. An example of modern flexible fixtures can be found in [52], where adaptive clamping units are used to reduce the distortion of the workpieces.…”
Section: Basic System Modelmentioning
confidence: 99%
“…Ivanov et al [54] developed new flexible fixtures to manufacture three different types of parts: levers, forks, and connecting rods. Ivanov et al [55] further analyzed and demonstrated the economic benefits of using flexible fixtures, which can effectively support small-batch productions with frequent changes of tools. An example of modern flexible fixtures can be found in [52], where adaptive clamping units are used to reduce the distortion of the workpieces.…”
Section: Basic System Modelmentioning
confidence: 99%